Study of Developmental Toxicity of Bromelain on Brine Shrimp (Artemia salina): Research Article (Journal of Pharma Insights and Research, 2024)
This study investigated the acute effects of bromelain on brine shrimp (Artemia salina) development and survival. Brine shrimp nauplii were exposed to varying concentrations of bromelain (1-800 μg/mL) for 24 hours. Mortality rates, growth patterns, and morphological changes were assessed. Results showed a dose-dependent increase in mortality, with 91.66% mortality at 800 μg/mL compared to 13.88% at 1 μg/mL. The lethal concentration (LC50) of bromelain was determined to be approximately 100 μg/mL. Morphological analysis revealed developmental retardation at the Instar II stage, with the formation of small vesicles observed microscopically. Growth measurements indicated minimal differences in developmental progression across treatment groups, with lengths ranging from 455-484 μm compared to 500 μm in controls. The study demonstrates that acute bromelain exposure exhibits toxic effects on brine shrimp, impacting survival and development. These findings suggest that brine shrimp may serve as a useful invertebrate model for preliminary toxicity screening of bromelain and potentially other proteolytic enzymes